MANIFESTASI KASIH DAN KEADILAN ALLAH: KAJIAN ETIS-TEOLOGIS TENTANG KEKERASAN - Heryson Butar-Butar (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
Violent behaviour in the history of human civilization has existed as old as human existence itself. Attempts to eradicate violent behaviour are futile because violence has a positive side when used with the right motivation, method and purpose. Applying violence with the reason to stop an injustice becomes an effective tool for creating a better life. The pros and cons regarding this matter are still the subjects of debate. This research aims to put forward a comprehensive ethical-theological thinking process to see the manifestation of God's love and justice for humans. The method used is qualitative, with an exploratory approach to obtain data and the context of the interpretation of violence in an ethical-theological scheme. The results of this study indicate that: humans are only responsible for minimizing the level of violence with the application of God's love and justice, violence does not always refer to the manifestation of the power of sin but human actions that have negative-destructive value when the violence is controlled and driven by corruption, and violence can have a value positive-constructive when owned and driven by God's love and justice.